2008
DOI: 10.1111/j.1752-0606.2008.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Experience of Rage: A Critical Feminist Analysis

Abstract: We conducted in-depth interviews with 37 incarcerated women on their experience of rage towards their intimate partner. Participants used specific criteria to distinguish their experience of rage from anger. Rage is described as an overwhelming experience with particular physiological and cognitive changes that takes control of a woman's emotions and actions. In contrast, anger is described as a controllable emotion with a specific termination point. Motivations for acting violently in rage with an intimate pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
(45 reference statements)
2
18
0
Order By: Relevance
“…Although some women may internalize abusive experiences in a highly contained way, which manifest through clinical diagnoses such as depression (McGuigan and Middlemiss 2005;Sullivan et al 2005) or anorexia-nervosa (Laporte and Guttman 2001), along with acts of self-mutilation (Currier 2004), other women may externalize those experiences through rage that involves acts of violence and aggression (Flemke 2006;Flemke and Allen 2008). What was learned from this particular group of women was that triggers for rage may be rooted in past wounds of abuse and other victimization.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although some women may internalize abusive experiences in a highly contained way, which manifest through clinical diagnoses such as depression (McGuigan and Middlemiss 2005;Sullivan et al 2005) or anorexia-nervosa (Laporte and Guttman 2001), along with acts of self-mutilation (Currier 2004), other women may externalize those experiences through rage that involves acts of violence and aggression (Flemke 2006;Flemke and Allen 2008). What was learned from this particular group of women was that triggers for rage may be rooted in past wounds of abuse and other victimization.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, research on the experience of rage depicts emotional precursors that quickly escalate prior to its detonation, such as feeling intense fear due to feeling threatened and feeling overwhelmed (Flemke 2006;Flemke and Allen 2008). As these intense emotions build and culminate, a sense of feeling emotionally and physically ''out of control'' occurs that often erupts in violence.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some of the variables that have been identified in the literature include the perceived threat of infidelity (Flemke & Allen, 2008;Goetz & Shackelford, 2006;Kaighobadi et al, 2009;Starratt, Goetz, Shackelford, McKibbin, & Stewart-Williams, 2008), the perceived threat of a loss of control over a partner (Hamby, 1996;Stuart et al, 2006;Sugihara & Warner, 2002), and shame-inducing experiences (i.e., public scolding, random punishment, and generic criticism; Dutton, van Ginkel, & Starzomski, 1995;Mills, 2008;Tangney, 1991). However, most theoretical and empirical literature analyzing these theories has focused on men's violence against women in partner relationships.…”
Section: Intimate Partner Violence Contexts and Risk Factorsmentioning
confidence: 96%
“…In a sample of college students, Bookwala and Zdaniuk (1998) found that attachment anxiety tendencies were associated with dating violence. Follingstad, Bradley, Helff, and Laughlin (2002) found that attachment anxiety in a college sample was indirectly related to dating violence through anger and control. Others have shown that attachment anxiety in either partner increases the likelihood of abuse (Henderson, Bartholomew, Trinke, & Kwong, 2005), although attachment may be more predictive of IPV for avoidantly attached individuals when they are paired with an anxiously attached partner (Bond & Bond, 2004;Doumas, Pearson, Elgin, & McKinley, 2008).…”
Section: Attachment and Intimate Partner Violencementioning
confidence: 97%